Paleo- and rock magnetism of the Central Atlantic Magmatic Province (CAMP) from Portugal: global-scale correlations and implications for the paleogeography of Iberia at 200 Ma - Fernandes, Susana de Lurdes Alves (2014)
Tese de mestrado em Ciências Geofísicas, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2013